2014
DOI: 10.3389/fnbeh.2014.00256
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of sertraline in a predator exposure animal model of post-traumatic stress disorder

Abstract: Serotonin (5-HT), norepinephrine (NE), and other neurotransmitters are modulated in post-traumatic stress disorder (PTSD). In addition, pro-inflammatory cytokines (PIC) are elevated during the progression of the disorder. Currently, the only approved pharmacologic treatments for PTSD are the selective-serotonin reuptake inhibitors (SSRI) sertraline and paroxetine, but their efficacy in treating PTSD is marginal at best. In combat-related PTSD, SSRIs are of limited effectiveness. Thus, this study sought to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 51 publications
(67 reference statements)
4
40
0
Order By: Relevance
“…In particular, in line with the literature and our hypothesis, treatment in a stressful condition overall led to an anti-inflammatory response (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015). By contrast, fluoxetine treatment in an enriched condition led to an increased expression of inflammatory genes.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…In particular, in line with the literature and our hypothesis, treatment in a stressful condition overall led to an anti-inflammatory response (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015). By contrast, fluoxetine treatment in an enriched condition led to an increased expression of inflammatory genes.…”
Section: Resultssupporting
confidence: 75%
“…These findings indicate that fluoxetine increases the overall inflammatory milieu in the enriched condition, while exerting an opposite effect in the stressful condition. The latter result is in line with previous studies showing that fluoxetine, when administered to mice exposed to a stressful environment, overall reduces hippocampal expression of pro-inflammatory cytokines (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015).…”
Section: Fluoxetine Affects Hippocampal Inflammatory Mediatorssupporting
confidence: 81%
See 1 more Smart Citation
“…In an extension of their VA work, this group also reported that 5-HT levels were normalized with chronic treatment of psychosocially stressed rats with a selective serotonin reuptake inhibitor (SSRI) (Wilson et al, 2014b). Perhaps most important, NE levels remained significantly increased in stressed rats treated with sertraline, which may explain why sertraline provided no benefit in relation to anxiety-like behavior in the stressed rats (Wilson et al, 2014b).…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Perhaps most important, NE levels remained significantly increased in stressed rats treated with sertraline, which may explain why sertraline provided no benefit in relation to anxiety-like behavior in the stressed rats (Wilson et al, 2014b).…”
Section: Accepted Manuscriptmentioning
confidence: 98%